Synthesis of unsymmetrical benzotrichalcogenophenes by N-heterocyclic carbene–palladium-catalyzed intramolecular direct C3-arylation of chalcogenophenes. Issue 12 (24th January 2018) - Chen, Shi-Yen; Pao, Yu-Chieh; Sahoo, Santosh K.; Huang, Wen-Chia; Lai, Yu-Ying; Cheng, Yen-Ju
Abstract : A series of new unsymmetrical benzotrichalcogenophenes (BTCs) were synthesized by the Pd–N-heterocyclic carbene catalyzed intramolecular C3-arylation of furan, thiophene, selenophene and tellurophene units. Abstract : A series of new unsymmetrical benzotrichalcogenophenes (BTCs) were synthesized by the Pd–N-heterocyclic carbene catalyzed intramolecular C3-arylation of furan, thiophene, selenophene and tellurophene units. This is the first time that a C3-direct arylation of selenophene and tellurophene moieties has ever been demonstrated.